2004
DOI: 10.2337/diacare.27.3.746
|View full text |Cite
|
Sign up to set email alerts
|

Use of Arterial Transfer Functions for the Derivation of Central Aortic Waveform Characteristics in Subjects With Type 2 Diabetes and Cardiovascular Disease

Abstract: OBJECTIVE -Optimal blood pressure control in subjects with diabetes reduces cardiovascular complications. There is theoretical benefit in the assessment of central aortic waveforms including the augmentation index, which is taken as a putative index of stiffness. Transfer functions may be used to reconstruct aortic from radial pressure waveforms; however, a single generalized transfer function may not be appropriate for all patients. We aimed to evaluate the technique in subjects with diabetes.RESEARCH DESIGN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 19 publications
2
45
0
2
Order By: Relevance
“…Regression coefficients were compared with z statistics. To ensure that comparisons of P2-versus GTF-derived aortic BP-target organ relations were not confounded by possible inaccuracies in the use of a GTF in diabetics (and, thus, the need for a diabetes-specific transfer function) 17 or because of inaccuracies in the use of a transfer function that is sex inappropriate (and, hence, a possible need for sex-specific transfer functions), 18 sensitivity analysis was conducted in nondiabetics (and those with an HbA 1C Յ6.1%) and in men separate from women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regression coefficients were compared with z statistics. To ensure that comparisons of P2-versus GTF-derived aortic BP-target organ relations were not confounded by possible inaccuracies in the use of a GTF in diabetics (and, thus, the need for a diabetes-specific transfer function) 17 or because of inaccuracies in the use of a transfer function that is sex inappropriate (and, hence, a possible need for sex-specific transfer functions), 18 sensitivity analysis was conducted in nondiabetics (and those with an HbA 1C Յ6.1%) and in men separate from women.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to tonometry performed at alternative sites, which often cannot be reliably applied (eg, in obesity), radial tonometry, together with a GTF, provides an easy and reproducible method of deriving aortic BP. However, the GTF may be limited in certain circumstances, [15][16][17][18] and the actual GTF in the SphygmoCor device, although validated, has not been described and is, therefore, not available for careful scrutiny by the general scientific community. In the present study we show that using the SphygmoCor device, P2-derived BPc, which does not require complex transformations using a GTF, is associated with target organ changes independent of brachial BP, that these relationships are as strong as brachial BP-independent GTF-derived BPc-target organ changes, and that P2-derived BPc-target organ relations survive adjustments for nursederived brachial BP measurement, whereas gold-standard 24-hour, day, or night brachial BP-target organ relations do not.…”
Section: Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…13,[23][24][25] However, the invasive nature of these validation studies limits them to individuals undergoing clinically indicated cardiac catheterization and is not suited to examining the transfer function in at-risk subjects in whom such investigations are not justified. Differences have been described previously in the peripheral-to-central transfer function between men and women, 26 diabetic and nondiabetic populations, 27 individuals with and without coronary disease, 28 and before and after exercise, 16 and the effects of CKD on vascular function might, therefore, be expected to also impact on the transfer function in this population. There is no single agreed method of validation, and so we have attempted to study the effect of renal function on a range of factors, both in the time domain and frequency domain.…”
Section: Discussionmentioning
confidence: 99%